The effect of entrepreneurial traits in relation to technology entrepreneurship education and entrepreneurial behavior / Rohana Ngah ... [et al.] - Ngah, Rohana; Buyong, Siti Zahrah; Junid, Junainah; Mohd Lajin, Noor Faizah (Universiti Teknologi MARA Cawangan Selangor, 2018)
Entrepreneurship has become an important national agenda especially in creating young entrepreneurs. This paper aims to determine entrepreneurial behavior through technology entrepreneurship education and entrepreneurial personality traits of students from the Science and Technology clusters. The purpose of technology entrepreneurship as a subject is to encourage students to embark on their entrepreneurship venture using technology. A total of five hundred and ninety-two usable questionnaires were collected at the end of the semester. Partial Least Square was utilized to explore the relationship of variables. Entrepreneurial personality traits mediated the relationship between technology entrepreneurship education and entrepreneurial behavior despite the lack of business exposure among students. Technology entrepreneurship education helps to foster entrepreneurial behavior among students. In addition, knowing students' entrepreneurial personality traits further strengthens entrepreneurial behavior.